2017
DOI: 10.5539/ijel.v7n1p215
|View full text |Cite
|
Sign up to set email alerts
|

The Study of the Metalinguistic Knowledge of English by Students in an Intensive and a Traditional Course

Abstract: The goal of the current research was to study the relationship among learning contexts and, levels of metalinguistic knowledge of the Iranian intermediate EFL learners. This research explores the level of learners'metalinguistic knowledge in English in two different contexts (traditional and intensive courses). Participants included 44 intermediate students at Shoukoh Language Institute, Zanjan, Iran. The selection violated the randomization criterion, thus the quasi-experimental was taken for the current stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Supporting the study, from Nazarian & Izadpanah, (2017), the outcomes showed that there was a substantial difference in two groups of participants' semantic test performance. A rigorous English course had a significant positive impact on the students' Semantic Knowledge in English (SKE).…”
Section: Foreign Studiesmentioning
confidence: 64%
“…Supporting the study, from Nazarian & Izadpanah, (2017), the outcomes showed that there was a substantial difference in two groups of participants' semantic test performance. A rigorous English course had a significant positive impact on the students' Semantic Knowledge in English (SKE).…”
Section: Foreign Studiesmentioning
confidence: 64%
“…Students found the serious-interesting speech the most interesting, and more interesting than the interesting-humorous speech. Gruner found that learning improved along interest but not along humor lines (Gruner, 1970;Nazarian & Izadpanah, 2017). The limitations described in the review of this study in the Instructor Evaluations section above apply to the learning results as well: since the dull speeches were performed differently than interesting speeches, this may have created a confounding variable, an idea pointed out by Mayer in the Voice Principle (Mayer, 2009).…”
Section: Previous Studies About the Ineffectiveness Of Humorous Moviementioning
confidence: 86%
“…Reviewing the literature, the findings from recent research on MLK in Iranian contexts have shown a much higher focus on such knowledge in L2 learning and use (Nazarian & Izadpanah, 2017;Modirkhamene, 2008;Seifoori, 2015) and teachers' MLK and the factors contributing in its development seems an area that has hitherto received only peripheral attention in research on MLK. Moreover, no study thus far has examined a comparison between school teachers and private language institute teachers in this regard.…”
Section: Empirical Studies On Mlkmentioning
confidence: 99%